MODULES HAVING (WEAK-S*) PROPERTY - Yaseen, Sahira (Iraqi Journal of Science, 2024)
Let R be a non zero ring with identity and let M be a non zero module over R. AnR-module M is called cosingular if Z*(M)=M where Z*(M)=m ∈ M, mR<<E(M),in this paper we introduce the concept that an R-module M is weak-cosingular ifZ*(M)≤e M. and we call that an R-module has (weak-S*)property if every submoduleN of M contains a direct summand K of M such that K≤N and N/K is weakcosingular.And we study the properties of this kind of modules, and the relationbetween this modules and other kind of modules.